1981
DOI: 10.1128/mmbr.45.1.9-51.1981
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage T3 and bacteriophage T7 virus-host cell interactions.

Abstract: Restriction Analysis of Phage Deoxyribonucleic Acid (DNA) The utility of sequence-specific restriction endonucleases for physical mapping and sequence analysis of genomes and for gene cloning (272, 327, 328, 394, 395, 466) has had its impact also MICROBIOL. REV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 312 publications
(524 reference statements)
0
31
0
1
Order By: Relevance
“…An interesting parallel is found in coliphage T7, in which selection has removed recognition sequences for many E. coli-based restriction systems, with the exception of EcoPI. The EcoPI cut site overlaps the T7 primase binding sequence, illustrating preservation of function outweighing selection pressure (22,33). An alternative explanation for the presence of AT-rich palindromes in HF2 is that there may be few halobacterial restriction systems that target AT-rich DNA, a reflection of the GC-rich nature of halobacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting parallel is found in coliphage T7, in which selection has removed recognition sequences for many E. coli-based restriction systems, with the exception of EcoPI. The EcoPI cut site overlaps the T7 primase binding sequence, illustrating preservation of function outweighing selection pressure (22,33). An alternative explanation for the presence of AT-rich palindromes in HF2 is that there may be few halobacterial restriction systems that target AT-rich DNA, a reflection of the GC-rich nature of halobacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Since the original description of phage-coded activities that prevent T7 and T4 restriction (10,26), this phenomenon has been reported for T3, T5, and bacillus phage NR2 (for review, see reference 17). More recently, the direct interaction of the T7 antirestriction protein with the host-restricting enzyme has been nicely demonstrated (19).…”
Section: Discussionmentioning
confidence: 89%
“…Bacteriophage T7 is an attractive system for the study of DNA metabolism and genetic regulation. This phage has been extensively characterized genetically (4,22,23), and its genome consists of a double-stranded DNA molecule which codes for about 50 proteins. The entire genomic DNA molecule has recently been sequenced (J. Dunn and F. W. Studier, J. Mol.…”
mentioning
confidence: 99%
“…Genetic recombination of T7 has been studied in vivo (3, 5, 7-9, 19, 20, 24, 25). From these studies, it was concluded that T7 recombination in vivo requires the products of T7 gene 3 (endonuclease), gene 4 (DNA primase), gene 5 (DNA polymerase), and gene 6 (exonuclease). Recombination is independent of the host and phage ligase, DNA packaging, and maturation functions.…”
mentioning
confidence: 99%